Perancangan Ulang Tata Letak Fasilitas Produksi Beton menggunakan Metode Activity Relationship Chart (ARC) di PT. XYZ - Akmal Nasir; Galih Mahardika Munandar; Muhammad Nur Wahyu Hidayah; Alifta Dicasani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Material handling is a term for transportation or transport activities carried out by industrial companies, which involve moving raw materials, semi-finished goods or finished goods from one location to another predetermined location. Apart from that, material handling is also important in quality control, where 3-5% of damaged goods are caused by material handling. The aim of this research is to identify and redesign the layout conditions of concrete production facilities at PT. XYZ. The method of this research is the Activity Relationship Chart (ARC), Activity Relationship Daigram (ARD) and Total Closeness Rating (TCR) methods. In the current layout conditions, the sand warehouse and crushed stone warehouse work stations should be close to the two hoppers, namely the batching plant hopper and the asphalt mixing plant hopper, but in the actual conditions these two work stations are not close to each other. In the new facility layout there are changes and relocation of work stations based on the degree of proximity. Future research is expected to consider the amount of time generated during the material handling process and also consider cost aspects during the process of designing changes to the facility layout.